Potassium Alkoxide as an Efficient Catalyst for Nucleophilic Perfluoroalkylation: Attempt at Anion-Controlled Enantioselective Insertion of a Trifluoromethyl Group - Yurino, Taiga; Yamashita, Hiroyuki; Shan, Yuanrong; Wu, Zhen; Ohkuma, Takeshi (Synlett, 2022)
Potassium alkoxide was found to be a highly active catalyst for the nucleophilic trifluoromethylation of carbonyl compounds. The catalytic system was successfully applied to the reactions of both aldehydes and ketones, affording the corresponding trifluoromethylated products in high yields at low catalyst loadings (0.1–0.01 mol%) in several solvents, such as THF, toluene, and CH2Cl2. In addition, the potassium salt of a Ru(II) complex bearing an (S)-2,2′-bis[bis(3,5-dimethylphenyl)phosphinyl]-1,1′-binaphthalene [(S)-XylBINAP] ligand and two l-threoninate ligands, prepared in situ, catalyzed the enantioselective trifluoromethylation of aromatic aldehydes, although the ee values were not satisfactory (less than 20%).
Keywords: trifluoromethylation; potassium tert-butoxide; ruthenium catalysis; trifluoromethyltrimethylsilane; asymmetric catalysis; carbonyl compounds